Trends in Disease Burden of Chronic Lymphocytic Leukemia at the Global, Regional, and National Levels From 1990 to 2019, and Projections Until 2030: A Population-Based Epidemiologic Study - Ou, Yang; Long, Yichen; Ji, Lili; Zhan, Yanxia; Qiao, Tiankui; Wang, Xiangdong; Chen, Hao; Cheng, Yunfeng (Frontiers in Oncology, 2022)
Background The prognosis of chronic lymphocytic leukemia (CLL) has been improved dramatically, but there are scarce studies focusing on the disease burden of CLL in the global scope. We aimed to assess the accurate assessment of the disease burden of CLL that may provide more detailed epidemiological information for rational policies. Methods All data used in our study came from the Global Burden of Disease (GBD) study 2019. Incident cases, death cases, disability-adjusted life-years (DALYs), and their corresponding age-standardized rates (ASRs) from 1990 to 2019 were used to describe the burden of CLL. Data about attributable risk factors were also extracted and analyzed. Bayesian age-period-cohort (BAPC) models were used to assess and project the incidence and mortality rates till 2030. Results Globally, the incidence of CLL had been increasing. Deaths and DALYs decreased slightly. The burden of death and DALY is affected by SDI. The incidence rate, death rate, and DALY rate of CLL increased significantly with age. Male-to-female ratios of incidence rates varied in different SDI quintiles. Smoking, high body mass index, and occupational exposure to benzene or formaldehyde were the potential risk factors related to CLL. Global ASIRs might tend to increase until 2030, while ASDR would decrease until 2030. Conclusion: The disease burden of CLL decreased in higher SDI countries but increased in lower ones. Strategies about early detection of asymptomatic CLL, the introduction of novel drugs, and against attributable factors should be implemented to reduce CLL burden.